Delayed emergence of subdiffraction-sized mutant huntingtin fibrils following inclusion body formation. (2016) - Sahl, Steffen J.; Lau, Lana; Vonk, Willianne I. M.; Weiss, Lucien E.; Frydman, Judith; Moerner, W. E.
Abstract: Aberrant aggregation of improperly folded proteins is the hallmark of several human neurodegenerative disorders, including Huntington's Disease (HD) with autosomal-dominant inheritance. In HD, expansion of the CAG-repeat-encoded polyglutamine (polyQ) stretch beyond ~40 glutamines in huntingtin (Htt) and its N-terminal fragments leads to the formation of large (up to several μ m) globular neuronal inclusion bodies (IBs) over time. We report direct observations of aggregating Htt exon 1 in living and fixed cells at enhanced spatial resolution by stimulated emission depletion (STED) microscopy and single-molecule super-resolution optical imaging. Fibrils of Htt exon 1 arise abundantly across the cytosolic compartment and also in neuritic processes only after nucleation and aggregation into a fairly advanced stage of growth of the prominent IB have taken place. Structural characterizations of fibrils by STED show a distinct length cutoff at ~1·5 µ m and reveal subsequent coalescence (bundling/piling). Cytosolic fibrils are observed even at late stages in the process, side-by-side with the mature IB. Htt sequestration into the IB, which in neurons has been argued to be a cell-protective phenomenon, thus appears to saturate and over-power the cellular degradation systems and leaves cells vulnerable to further aggregation producing much smaller, potentially toxic, conformational protein species of which the fibrils may be comprised. We further found that exogenous delivery of the apical domain of the chaperonin subunit CCT1 to the cells via the cell medium reduced the aggregation propensity of mutant Htt exon 1 in general, and strongly reduced the occurrence of such late-stage fibrils in particular.